First Stereoselective Total Synthesis of Tumonoic Acid A and its Derivatives - Nagalatha, G.; Narala, Siva Ganesh; Narsaiah, A. Venkat (SynOpen, 2018)
An efficient protecting-group-free synthesis of tumonoic acid A and its derivatives has been accomplished. The synthesis started from commercially available n-octanal and employs the magnesium chloride catalysed anti-aldol reaction under the Evans protocol as the key step. Ethyl tumonoate A is a new tumonoic acid derivative with anti-inflammatory activity and inhibitory activity towards calcium oscillations in neocortical neurons.
Keywords: n-octanal; Wittig reaction; chiral auxiliary; hydrolysis; coupling